Image Assisted Percutaneous Intramedullary Fixation of Radius and Ulna Shaft Fractures in older Children - Sohail Iqbal Shiekh , Abdul Basit , Awais Ahmed , Javaid Iqbal , Saba Sohail Shiekh ,Imran Sohail Shiekh (Journal of Rawalpindi Medical College, 2013)
Background: To assess outcome and complications associated with percutaneous Intramedullary Kirschner-wire fixation for fracture of radius and ulna diaphyseal fractures in older children. Methods: In this prospective study 17 boys and 7 girls, aged 8-14 years, with unstable displaced fractures of shaft of radius and ulna, were enrolled. All the cases were treated with percutaneous Intramedullary Kirchner wire fixation. The cases were followed up for 6 months with evaluation by repeated X- rays to assess the level of union and function which were graded as perfect, good, fair and poor. Results: All fractures united in acceptable alignment. At final assessment there were 17 perfect, 6 good and 2 fair. There was no case with poor alignment . The fair clinical outcome was higher in children above 10 years of age. Conclusion: Intramedullary k-wire fixation plus cast stabilization can provide precise and good fracture reduction, maintains stabilization for fracture healing and results in minimal deformity. It is cost effective and facilitates easy removal of implants after treatment